2017
DOI: 10.21577/0103-5053.20170143
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Bentonite and Vermiculite after the Creation of Structural Defects through an Acid Leaching Process

Abstract: The synthesis and use of functionalized materials is growing every year. Thus, this work presents a methodology for the functionalization of bentonite and vermiculite after the acid leaching of the raw materials. Leaching was performed with sulfuric acid (H 2 SO 4 ), and the functionalization was performed with (3-mercaptopropyl)trimethoxysilane (MPTS), which was oxidized after being anchored to the support. Compared to the results in the literature for directly functionalized raw bentonite, the materials had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…XRD patterns of natural bentonites (Bent) (Figure 2a,b) showed peaks related to montmorillonite (Mt), Kaolinite (K) and quartz (Q) cristals, an importante fingerprint for compounds that belong to the smectite group [34,44,50,60].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…XRD patterns of natural bentonites (Bent) (Figure 2a,b) showed peaks related to montmorillonite (Mt), Kaolinite (K) and quartz (Q) cristals, an importante fingerprint for compounds that belong to the smectite group [34,44,50,60].…”
Section: Resultsmentioning
confidence: 99%
“…The derivative curves (Figure 3b–d) provided information on the different steps of the decomposition of the natural and modified clays. At temperatures below to 150 °C there was a weight loss attributed to desorption of water adsorbed on the external surface or coordinated with interchangeable cations between the clay mineral layers [34,41,44,50]. That weight loss can also be attributed to the inclusion of hydrated HPMo in the pores of the supports [41,59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the treatment with minerals acids significantly changed their textural characteristics. This can expand their applications to include environmental protection [14,15], catalytic cracking of petroleum [16], catalyst supports in many chemical processes and detergent in paper industries and textile fabrications [17][18][19]. In fact, the most applications of these clays are bleaching, purification and stabilization of vegetable oils.…”
Section: Introductionmentioning
confidence: 99%
“…The materials pore size, surface area and pore volume are obtained by N 2 adsorption. Nitrogen adsorption‐desorption isotherms of vermiculite and 5 wt%‐A/B‐V4 composite are presented in Figure a and Figure b, which possessed a type I isotherm corresponding to microporous solids . Besides, the pore size distribution is shown in Figure c, and it can be observed that the pore diameter of vermiculite is mainly 4 nm.…”
Section: Resultsmentioning
confidence: 99%